Efektifitas Menakar Keadilan dalam Kebijakan Pemberian Remisi Bagi Koruptor - Edi Sofwan (PLEDOI (Jurnal Hukum dan Keadilan), 2022)
Giving remission to corruptors is an irrelevant policy. The effectiveness of measuring justice against extraordinary crimes (corruption) cannot be interpreted as a tool to reduce punishment or change the sentence that has been determined by the court so that remissions are not immediately given to prisoners in corruption cases. Then, the arrival of Covid-19 impacted economic difficulties for all elements of Indonesian society; however, sadly, in this Covid-19 disaster situation, there were elements of the political elite who smuggled the social assistance funds. So, granting remissions to corruptors should be removed because it affects the community at significant, human rights that are closely related to prisoners, one of which is the provision of remissions, the provisions of Article 14 paragraph (1) of Law Number 12 of 1995 concerning Corrections states that one of the rights of the convict is to get a reduction in the criminal period (remission). The method that will be used is the normative juridical research method and the research materials used in this research by using studies on laws and regulations, books, journals, news, and relevant information that discusses the effectiveness of measuring justice against corruption cases in social assistance during a pandemic. Covid-19. The results of this study are: The concept of justice for officials who have committed corruption Social Assistance Funds (BANSOS) is an extraordinary crime that impacts the sustainability of the community and should not be given remission for officials who misuse the aid funds.